Pengaruh Edukasi Pengguna, Kepuasan Pelanggan, dan Kinerja Organisasi terhadap Keberhasilan Implementasi ERP - Natasya Khoirunisah; Vinola Herawaty (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study aims to analyze the influence of customer education, customer satisfaction, and organizational performance on the success of Enterprise Resource Planning (ERP) implementation. The study employed a quantitative approach using a survey method through the distribution of Likert-scale questionnaires to 236 respondents who use ERP systems. The data were analyzed using validity and reliability tests, as well as multiple linear regression analysis. The results indicate that customer education has a significant but negative effect on the success of ERP implementation. Customer satisfaction does not have a significant effect on ERP implementation success. Meanwhile, organizational performance has a positive and significant effect and is the most dominant variable in explaining ERP implementation success. Simultaneously, the three variables account for 91.0% of the variation in ERP implementation success. These findings confirm that the success of ERP implementation is more strongly determined by the system’s ability to improve organizational performance. Therefore, companies should focus their implementation strategies on optimizing operational benefits and evaluating the effectiveness of user education.